FULL MAGAZINE OF SCIENCE NATURE, VOL. 1(1), DECEMBER 2018 - science nature (SCIENCE NATURE, 2018)
This file contains the whole published papers in SCIENCE NATURE VOLUME 1, ISSUE 1, dated on 13rd December 2018.